SURVEY PAPER ON PRIVACY IN LOCATION BASED SEARCH QUERIES. - Phaltane Anjali .D; Pathan Farheen..F; Prof.Prabhudev (International Journal of Innovations in Engineering Research and Technology, 2021)
Due to tremendous growth in mobile phones, the market for Location Based Services is growing fast. Many mobile phone applications uses location based services such as nearest store finder, car navigation system etc. Location –Based Services provides services to mobile device users based on the location information as well as data profile of the users. Using these services mobile users retrieve information about nearest POI. This involves location and data profile of the user’s to be misused. In order to protect user’s private information many solutions are offered but most of them only addressed on snapshot and no support for continuous query and MQMO .Some papers addressed MQMO but fails to provide privacy. This paper focuses on MQMO and also protect user’s private information using PIR (private information retrieval) .